Problems and Suggestions in the Development of Green Finance Under the “Dual Carbon Target” (Asian Business Research, 2022)
To achieve carbon peak, carbon neutrality, referred to as “dual carbon target”, is china's solemn commitment to the international community, but also a broad and profound economic and social change. As a link and bridge of high- quality economic development, green finance plays a crucial role in it. Under the goal of „double carbon‟, this paper studies that green finance can provide sufficient power for the high-quality development of national economy, and at the same time, it looks for the main problems existing at the present stage and gives corresponding countermeasures and suggestions.